Adjustment dynamics and business cycle heterogeneity in the EMU: Evidence from estimated DSGE models - Massimo Giovannini; Stefan Hohberger; Marco Ratto; Lukas Vogel (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
The paper reviews adjustment dynamics in the EMU on the basis of estimated DSGE models for four large EA Member States (DE, FR, IT, ES). We compare the response of the four countries to identical shocks and find a particularly strong response of employment and wages in ES, a high sensitivity of IT to investment-related shocks, and a comparatively strong impact of global shocks on the DE economy. We also perform counterfactual exercises that apply the estimated shocks and parameters for ES to DE, FR, and IT. The counterfactual simulations suggest that differences in shocks have been important for GDP growth differentials, and together with structural differences also contributed to differences in employment fluctuations across the four countries considered.
Keywords: E32; F41; F44; F45; 330; Estimated DSGE; adjustment dynamics; business cycles; EMU; counterfactuals